Potensi Pajak Pada Usaha Mikro Kecil Menengah (UMKM) - Nurlinda Nurlinda; Junus Sinuraya (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2020)
The purpose of this study was to determine, calculate and analyze the economic potential contained in Rujak MSMEs in Simpang Jodoh Kab. Deli Serdang, to calculate the potential tax imposed on the gross turnover of MSMEs. This MSMEs is a group of culinary traders in the Tembung area, Percut Sei Tuan District. Referring to the potential of rujak MSMEs, if managed properly, it will increase local government revenue from the tax and retribution sector. This type of research is quantitative. The sampling technique uses saturated samples. The types of data used are primary data and secondary data. Methods of data collection using questionnaires, interviews and documentation. The data analysis used was descriptive statistics. The results of the study found that there was a potential tax on MSMEs Rujak. The amount of tax potential owned by MSMEs with the lowest conventional sales for conventional sales is Rp. 42,205,800 while the highest potential tax is Rp. 45,938,000 per year. The amount of tax potential that MSMEs have when making sales using social media and collaborating with go-food or grab-food applications increases to Rp. 56,057,040 for the lowest sales and 67,551,120 for the highest condition. The increase in tax potential is in the range of 132.82% to 147.05% when the Rujak MSMEs use media and online applications in marketing their products.